2017
DOI: 10.18632/oncotarget.22442
|View full text |Cite
|
Sign up to set email alerts
|

LCZ696, a promising novel agent in treating hypertension (a meta-analysis of randomized controlled trials)

Abstract: BackgroundTo determine the effectiveness and safety of LCZ696 for the clinical treatment of hypertension, we performed a meta-analysis of the previous clinical trials.MethodsRelevant English articles and randomized controlled trials were searched in Pubmed, Embase, EBSCO, Cochrane base and ClinicalTrials.gov. The last search date was July 20th, 2017.ResultsCompared with 20mg olmesartan, 200mg and 400mg LCZ696 outperformed olmesartan in terms of reducing mean sitting systolic blood pressure, mean ambulatory sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In our meta-analysis, we found that LCZ696 (100, 200, and 400 mg) produced significantly greater reductions in SBP, DBP, 24 h ASBP, and 24 h ADBP than ARBs alone in hypertensive patients. These results are consistent with the meta-analyses of Ye et al [21] and Zhao et al [23]. Compared with ARBs alone, LCZ696 causes a greater reduction in blood pressure, mainly attributed to RAS inhibition occurring simultaneously with neprilysin inhibition.…”
Section: Effects Of Lcz696 On Blood Pressure 597supporting
confidence: 91%
See 1 more Smart Citation
“…In our meta-analysis, we found that LCZ696 (100, 200, and 400 mg) produced significantly greater reductions in SBP, DBP, 24 h ASBP, and 24 h ADBP than ARBs alone in hypertensive patients. These results are consistent with the meta-analyses of Ye et al [21] and Zhao et al [23]. Compared with ARBs alone, LCZ696 causes a greater reduction in blood pressure, mainly attributed to RAS inhibition occurring simultaneously with neprilysin inhibition.…”
Section: Effects Of Lcz696 On Blood Pressure 597supporting
confidence: 91%
“…Ruilope et al [6] were the first to demonstrate the antihypertensive efficacy of LCZ696. Ye et al [21] showed that LCZ696 is more effective in reducing blood pressure than placebo. Ito et al [22] suggested that LCZ696 administration may be a promising therapeutic approach for Japanese patients with hypertension and renal dysfunction.…”
Section: Effects Of Lcz696 On Blood Pressure 597mentioning
confidence: 99%
“…Sacubitril/valsartan (LCZ696) is a first-in-class dual NEP inhibitor and ARB approved to reduce risk of cardiovascular death and hospitalizations in heart failure [100]. Sacubitril/valsartan produces greater blood pressure-lowering effects when compared with an ARB alone or placebo in controlled trials in essential hypertension [101], and may produce insulin-sensitizing effects in obesity hypertension [102]. The specific mechanisms underlying beneficial effects of this combination drug remain unclear but may include sympathoinhibition, improved endothelial and cardiac function, and anti-arrhythmic, antiatherosclerotic, and anti-thrombotic effects [103].…”
Section: Dual Neprilysin and Angiotensin Receptor Inhibitormentioning
confidence: 99%
“…Most of these prospective and double-blind clinical trials showed that LCZ696 achieved the target blood pressure better without significant adverse effects. In addition, several meta-analyses have concluded that LCZ696 may reduce arterial pressure more efficaciously than placebo, particularly the angiotensin receptor blocker (ARB), without increasing overall adverse events [17][18][19]. However, some meta-analyses included non-RCTs, retrospective articles, or unpublished studies [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several meta-analyses have concluded that LCZ696 may reduce arterial pressure more efficaciously than placebo, particularly the angiotensin receptor blocker (ARB), without increasing overall adverse events [17][18][19]. However, some meta-analyses included non-RCTs, retrospective articles, or unpublished studies [17,18]. We performed a meta-analysis including high quality RCTs to precisely determine the effectiveness and safety of LCZ696 for the treatment of high arterial pressure.…”
Section: Introductionmentioning
confidence: 99%